Pengaruh Model Pembelajaran Role Playing Bermuatan Cerita Ramayana terhadap Hasil Belajar IPS - Ni Nyoman Kurnia Wati (Edukasi: Jurnal Pendidikan Dasar, 2022)
This study aims to analyze the differences in social studies learning outcomes between students who take lessons with the Role-Playing learning model containing the Ramayana story and students who follow conventional learning models for fifth grade students in elementary school Cluster VII, Buleleng District. This type of research is a quasi-experimental study with a population of all fifth-grade students of elementary school cluster VII Buleleng District. While the research sample amounted to 93 people. It can be concluded that the application of the Role-Playing learning model containing the Ramayana story has a positive effect on the social studies learning outcomes of fifth graders in the elementary school of Cluster VII, Buleleng District.